Manfaat Vitamin D untuk Pemain Sepak Bola : Mini Literature Review - Yustika, Gaung Perwira; Santoso, Eko Budi; Hadi, Cholichul; Sumartiningsih, Sri (Media Ilmu Keolahragaan Indonesia, 2020)
Permainan sepakbola dicirikan dengan pola aktivitas yang berubah-ubah, olahraga dengan durasi yang panjang dengan intensitas yang tinggi dan aksi yang eksplosif seperti melakukan akselarasi, deakselarasi, merubah arah, melompat, dan menjegal yang tentunya memerlukan kerja yang tinggi dari daya tubuh. Di dalam pertandingan kebutuhan energi sangat tinggi, dipenuhi dengan metabolisme aerob dan anaerob, yang mana perlu dibarengi dengan asupan nutrisi berkualitas dalam bentuk mikronutrisi khususnya asupan/pemaparan vitamin D untuk pemain agar dapat menunjang dan menjaga performa permainan dari seorang pemain, terlebih pada level sepakbola elit. Vitamin D sendiri adalah suatu prekursor hormon yang memiliki peranan penting di dalam menjaga kesehatan tulang dan fungsi imunitas. Penemuan reseptor vitamin D pada sel otot rangka manusia telah membawa para ilmuwan fisiologi otot untuk menemukan peranan penting vitamin D dalam meregulasikan sintesis protein dan fungsi otot. Pada atlit sepakbola elit, terdapat kebutuhan konstan vitamin D di dalam memaksimalkan sintesis protein untuk memenuhi kebutuhan fisik dari latihan harian. Selain dari pemaparan sinar matahari vitamin D pun dapat didapatkan dari sumber makanan yang mengandung nutrisi ini (hewani dan nabati).Soccer was characterized with activity that changed periodically during the game, this sport has long duration and with high intensity dan explosive action like doing acceleration, deacceleration, changing direction, jumping, and tackling. Of course in order to doing that this sport needs high rate of physical performance of the players. In the match, energy requirements is very high, fulfill by aerob metabolism and anaerob, to help the metabolism regulation, micronutrien intake especially vitamin D intake/exposure for the players to support and maintain performance of soccer players, especially in the elite level. Vitamin D is a hormonal precursor that hold an important role to maintain bone health and imunity function. The discovery of vitamin D receptor in human skeletal’s cells made attention to Muscle Physiologyst in order to find a way how vitamin D regulated protein synsthesis and muscle function. For soccer elite athletes, there’s constant needs of vitamin D to built synthesis protein in order to support the physical requirements from daily training. Besides sunlight exposure, vitamin D can be acquired from dietary foods that contain this vitamin (animal and plant source).Soccer was characterized with activity that changed periodically during the game, this sport has long duration and with high intensity dan explosive action like doing acceleration, deacceleration, changing direction, jumping, and tackling. Of course in order to doing that this sport needs high rate of physical performance of the players. In the match, energy requirements is very high, fulfill by aerob metabolism and anaerob, to help the metabolism regulation, micronutrien intake especially vitamin D intake/exposure for the players to support and maintain performance of soccer players, especially in the elite level. Vitamin D is a hormonal precursor that hold an important role to maintain bone health and imunity function. The discovery of vitamin D receptor in human skeletal’s cells made attention to Muscle Physiologyst in order to find a way how vitamin D regulated protein synsthesis and muscle function. For soccer elite athletes, there’s constant needs of vitamin D to built synthesis protein in order to support the physical requirements from daily training. Besides sunlight exposure, vitamin D can be acquired from dietary foods that contain this vitamin (animal and plant source).